Intramolecular rotation in a porphyrin dimer controls singlet oxygen production. - Kuimova, M; Balaz, M; Anderson, H; Ogilby, P (2009)
The efficiency with which a conjugated porphyrin dimer photosensitizes singlet oxygen production is shown to depend on the excitation wavelength, particularly in a viscous medium. This unprecedented behavior reflects viscosity-dependent dynamics that serve to interconvert two excited singlet state conformations of the porphyrin dimer. The efficiency of intersystem crossing from the two singlet state conformations to a common triplet state is shown to be different. In a viscous medium, each excited state conformation can be prepared selectively. Hence, wavelength-specific irradiation of the porphyrin allows fine control over the concentration of the triplet state produced which, in turn, is reflected in the photosensitized yield of singlet oxygen. This property may be beneficial for many applications requiring the controlled release of an oxidizing species, e.g., microfabrication and singlet oxygen-mediated cell death.